Research on the Initiative Scientific Research and Innovation Behavior of Postgraduates: Based on the Theory of Planned Behavior - Wang, Hong; Yang, Chunhuai; Meng, Meichen; Zeng, Yaxue (Frontiers in Psychology, 2022)
In order to clarify the generative mechanism and influencing factors of graduate students’ willingness and behavior of initiative scientific research and innovation, this research builds a quantitative model consisting of six variables: academic interest, regulatory pressure, conditions for improving scientific research and innovation capabilities, willingness to take initiative in scientific research and innovation, promotion of achievements in scientific research, and initiative scientific research and innovation behavior. 684 valid questionnaires were distributed and collected through WeChat Moments. Descriptive statistical analysis, reliability and validity analysis, factor analysis, path analysis and conditioning analysis were conducted using SPSS and SEM structural equation model. The results showed that:1.Academic interest, regulatory pressure, and conditions for improving scientific research and innovation capabilities have a positive impact on the intention of initiative scientific research and innovation, but the impact of regulatory pressure is extremely insignificant.2.The willingness to take initiative in scientific research and innovation has a positive and significant impact on initiative scientific research and innovation behavior, and the promotion of achievements in scientific research plays a negative moderating effect .Finally, this paper puts forward suggestions on how to promote the initiative scientific research and innovation behavior of postgraduate students based on the research results.